Internalized smoking stigma in relation to quit intentions, quit attempts, and current e-cigarette use. Issue 3 (July 2017) - O'Connor, Richard J.; Rees, Vaughan W.; Rivard, Cheryl; Hatsukami, Dorothy K.; Cummings, K. Michael
Background: Reducing the social acceptability of smoking is associated with lowered smoking prevalence. However, denormalization strategies can also contribute to the stigmatization that some smokers may feel about their smoking. Smoking stigma may be more acute if smokers are also members of other stigmatized groups, such as racial/ethnic minorities. This study examined correlates of smoking self- and felt-stigma and discrimination, among current smokers. Methods: Participants were recruited in the United States via a national commercial consumer panel to complete a cross-sectional, Web-based survey. Participants were 1528 current cigarette smokers aged 14 and older. Measures included the Internalized Stigma of Smoking Inventory (ISSI), Heaviness of Smoking Index, quit intentions, past-year quit attempts, and current use of electronic cigarettes (e-cigarettes). Results: Self-stigma was significantly associated with higher intent to quit in the next 6 months (odds ratio [OR] = 2.47, P < .01) and in the next 30 days (OR = 4.21, P < .01), relative to no intention to quit, as well as having made 1 or 2 quit attempts in the past year (OR = 1.60, P < .01) or 3 or more quit attempts (OR = 1.74, P < .01) and associated with daily e-cigarette use (OR = 1.73, P < .05). Felt-stigma was positively associated with intent to quit in the next 30 days (OR = 1.54, P < .01), having made 3 or more quit attempts in the past year (OR = 1.35, P < .01), and both daily (OR = 2.05, P < .05) and some-day (OR = 1.30, P < .05) e-cigarette use. Discrimination was associated only with increased odds of daily e-cigarette use (OR = 1.83, P < .05). Conclusions: Smokers who reported greater feelings of stigmatization about their smoking were more likely to report having made recent quit attempts, report a stronger intention quit smoking in the future, and report use of e-cigarettes, suggesting that feelings of self-and felt-stigmatization are related to greater motivation to stop smoking.